Manipulation unraveled: a new framework to analyze the impact of tournament design on manipulation opportunities - Devriesere, K.; Goossens, D.; Willem, A. (International Journal of Sports Science & Coaching, 2025)
Manipulation in sports competitions is widespread, but knowledge about how tournament design creates opportunities for manipulation is limited and scattered. Therefore, the goal of this study is to first identify manipulation opportunities caused by the way tournaments are designed. Secondly, we analyze which tournament designs are most vulnerable and most robust towards each opportunity. Based on a thorough review of a broad range of literature, a framework is developed to categorize manipulation opportunities. The proposed framework consists of two dimensions: whether benefits are guaranteed, and whether cooperation is needed. If the possibility of manipulation cannot be avoided, we present remedies from the literature that mitigate these opportunities. Finally, we present a flowchart that shows the impact of tournament design on the occurrence of manipulation opportunities. This framework provides valuable insights for managers and practitioners who wish to limit manipulation in sports tournaments.